Modern Principles of Designing Oil , Gas and Gas Condensate Fields (Eurasian Research Bulletin, 2023)
This article describes the stages of designing the development of an oil and gas field, including mining, geological and technical conditions that are mainly taken into account when developing oil, gas and gas condensate fields, and the classification of each stage.